Support over Safety? Rethinking How Organizational Support Empowers Gen Z in The Workplace - Gita Widya Laksmini Soerjoatmodjo (Indonesian Psychological Research, 2025)
This study aims to examine the relationship between perceived organizational support (POS), psychological safety climate (PSC), and psychological empowerment (PE) among Generation Z employees. While previous literature emphasizes the importance of team-based psychological safety in fostering empowerment, this study investigates whether organizational-level support may play a more dominant role for Gen Z workers. A cross-sectional quantitative design was used, involving 403 Gen Z employees from various sectors in Indonesia. Data were collected through self-report questionnaires and analyzed using structural equation modeling in JASP. The results revealed that POS had a strong and significant direct effect on PE (β = 0.518, p < .001). POS also significantly predicted PSC (β = 0.586, p < .001), but the mediating role of PSC was not supported, as the path from PSC to PE was not statistically significant (β = 0.114, p = .054). These findings suggest that Gen Z employees are more empowered by structural support and responsive leadership than by psychological safety within team interactions. The study contributes to the evolving understanding of Gen Z in the workplace and offers practical implications for designing more effective empowerment strategies.